In-service Training and Character Development in Relation to Islamization Initiatives in Selected Islamic Integrated Schools in Selangor - Javeed, Nihal Muhammad; Othman, Azam (IIUM Journal of Educational Studies, 2023)
Integrated Islamic schools in Malaysia and elsewhere face acute problems in acquiring and developing teachers who facilitate the Islamization of education process as well as holistic character development (tarbiyatul akhlaq) of children. The purpose of this study is to assess the relationship between in-service teacher training programs with elements of Islamization, the character development of teachers, and their self-efficacy as murrabis in private integrated Islamic schools in Selangor. The study administered surveys to 161 teachers in six (6) integrated Islamic schools in Selangor. Due to Covid-19 related challenges in obtaining respondents, convenience and snowball sampling techniques were utilized. The study employed correlation analysis utilizing SPSS v21 statistical software to answer the research questions. A strong positive correlation was discovered between in-service training with Islamization elements and character development of teachers as well as with teachers’ self-efficacy as a murabbi. The value of this research lies in underscoring the importance and development of in-service training in empowering the teacher to Islamize acquired knowledge subjects as well as in empowering them to be effective murabbis. It provides a basis for future research, especially in the Malaysian context, on teacher performance as a murabbi and its impact on students. It would also highlight to policymakers and educational administrators the need to develop a structured professional development program on Islamization of curriculum and the development of murabbis.